2020
DOI: 10.1021/acs.jpclett.0c01708
|View full text |Cite
|
Sign up to set email alerts
|

Direct Spectroscopic Observation of the Hole Polaron in Lead Halide Perovskites

Abstract: The intrinsic photophysical origin of lead halide perovskites (LHPs) that are used successfully in optolectronic applications remains hotly debated. Here, by using ultrafast X-ray transient absorption spectroscopy, we successfully tracked the fate of photogenerated charge carriers at room temperature within the thin films of two classic LHPs, namely, MAPbBr 3 (MA = CH 3 NH 3 ) and FAPbBr 3 [FA = CH(NH 2 ) 2 ]. We clearly observed in both thin films that the hole polaron is formed by localizing the photogenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…[ 109 ] Alternative spectroscopic approaches have included optical Kerr effect spectroscopy and 2D spectroscopy, [ 84,110,111 ] both of which are also able to provide sub‐picosecond time resolution, as well as slower techniques such as X‐ray transient absorption, which can give insights into structural distortions in a material. [ 112–114 ] We would caution that, although these techniques can provide valuable information regarding ultrafast processes in metal‐halide semiconductors, in general there can be a variety of contributing signals at early times and great care needs to be applied when interpreting specific transient experimental signals.…”
Section: Experimental Approaches For Observing Polaronic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 109 ] Alternative spectroscopic approaches have included optical Kerr effect spectroscopy and 2D spectroscopy, [ 84,110,111 ] both of which are also able to provide sub‐picosecond time resolution, as well as slower techniques such as X‐ray transient absorption, which can give insights into structural distortions in a material. [ 112–114 ] We would caution that, although these techniques can provide valuable information regarding ultrafast processes in metal‐halide semiconductors, in general there can be a variety of contributing signals at early times and great care needs to be applied when interpreting specific transient experimental signals.…”
Section: Experimental Approaches For Observing Polaronic Effectsmentioning
confidence: 99%
“…Recent work has highlighted the importance of structural distortions in inducing polaron formation across MHPs, [ 25,114,138 ] and a crucial question with regards nanocrystals is whether such structural distortions, and thus polaron formation, are facilitated or inhibited by nanoscale structures, as is the case for quasi‐0D metal halides (discussed below). Given that temperature‐dependent PL studies have found LO‐phonon energies between ℏ ω LO = 14–33 meV for (FA/Cs)PbBr 3 nanocrystals, [ 139–141 ] similar to the value of 15 meV obtained for bulk FAPbBr 3 by Wright et al., [ 79 ] as well as a similar LO‐phonon couplings (45 meV in nanocrystal FAPbBr 3 , [ 140 ] as opposed to 60 meV in bulk [ 79 ] ), it is not fully clear how much fundamental change is caused by the formation of nanocrystals.…”
Section: Polarons In Metal‐halide Semiconductorsmentioning
confidence: 99%
“…30,31 Although the polaron hypothesis was frequently invoked to rationalize experimental observations in both organic and inorganic perovskites, the quantification of the associated local structural rearrangement is still missing. In hybrid organic− inorganic lead halide perovskites, local distortions around the Pb 32 and Br 33 sites were separately reported in time-resolved Xray absorption spectroscopy (TR-XAS) studies and ascribed to polaron formation, but an unambiguous identification of the associated structural fingerprint was not provided. Ultrafast electron diffraction on a MAPbI 3 thin film showed evidence of local rotational disorder of the PbI 6 octahedra arising from optical excitation, as a consequence of hot carrier−phonon coupling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The one mechanism up to now neglected in our analysis is carrier‐lattice interaction, which can induce the formation of large charged polarons, as well documented in literature. [ 11–20 ] Dressing charged carriers by lattice deformations brings two main consequences: the first one is that polarons are energetically stabilized with respect to free electrons and holes, meaning that they sit at lower energy and therefore effectively reduce the exciton binding energy; the second one is the heavier mass of polarons than free carriers, which increases the density of states making them entropically favored with respect to excitons. Both effects reduce the probability of exciton formation, as also inferred from the analytical expression of the modified Saha constant neq=knormalBTtruem˜normalp2π232 eEnormalb (Ep+ + Ep)knormalBT, in which the exciton binding energy E b is reduced by the stabilization energy for the two polarons ( E p + + E p − ), and truem˜eh is replaced by the much larger mass truem˜normalp=mp+mpmnormale + mnormalh, where m p+, p− and m e,h are the polaron and free carrier masses, respectively (see Experimental Section for derivation).…”
Section: Discussionmentioning
confidence: 99%